2018
DOI: 10.1093/ntr/nty226
|View full text |Cite
|
Sign up to set email alerts
|

Home Health and Community Care Workers’ Occupational Exposure to Secondhand Smoke: A Rapid Literature Review

Abstract: IntroductionAlthough many workers are protected from exposure to secondhand tobacco smoke (SHS), home health and community care workers enter domestic settings where SHS is commonly present. Little is known about the extent of SHS exposure among this occupational group.MethodsA rapid review to examine the literature on home health and community care workers’ exposure to SHS at work and identify research gaps. Systematic searches combining terms for SHS exposure (eg, “tobacco smoke pollution”) with terms for ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…The situation is likely to be similar in many countries where smoke-free measures are well developed and while much of this exposure takes place in home settings there is still considerable evidence that non-smokers are exposed in the workplace, cars and peripheral settings such as building entrances and outdoor areas of bars [21]. Recent work has shown that those employed in the prison sector continue to be occupationally exposed to SHS [23] as are health and community care workers who enter smokers’ homes to provide care [24]. The ‘SHS issue’ is not yet ‘solved’: the public health community needs to continue their efforts and consider further measures to protect non-smokers from SHS.…”
Section: Discussionmentioning
confidence: 99%
“…The situation is likely to be similar in many countries where smoke-free measures are well developed and while much of this exposure takes place in home settings there is still considerable evidence that non-smokers are exposed in the workplace, cars and peripheral settings such as building entrances and outdoor areas of bars [21]. Recent work has shown that those employed in the prison sector continue to be occupationally exposed to SHS [23] as are health and community care workers who enter smokers’ homes to provide care [24]. The ‘SHS issue’ is not yet ‘solved’: the public health community needs to continue their efforts and consider further measures to protect non-smokers from SHS.…”
Section: Discussionmentioning
confidence: 99%
“…The home-work environment presents OSH risks rarely found in facilities, including spaces too small or cluttered to perform care work safely, aggressive unrestrained pets, bedbugs and other pests, loaded firearms, needles used by the client or other household members and discarded around the home, tobacco smoking, clients smoking while on oxygen, slippery or unsafe surfaces indoors and outdoors, and transportation accidents during work travel [ 47 , 50 , 51 , 55 ••, 56 , 57 ••].…”
Section: Home Care Job Hazardsmentioning
confidence: 99%
“…Current guidance and policy measures used by Health Boards and Social Care providers to assess and manage the risks to health from SHS are fragmented and often poorly understood. Evidence suggests that SHS exposure is a real concern for many domiciliary workers ( Angus and Semple, 2019 ) who feel left behind in terms of exposure to SHS when almost all other workers are protected through legislation.…”
Section: Introductionmentioning
confidence: 99%